SIRT1 regulates the neurogenic potential of neural precursors in the adult subventricular zone and hippocampus. Issue 5 (13th February 2013) - Saharan, Sumiti; Jhaveri, Dhanisha J.; Bartlett, Perry F.
Abstract Within the two neurogenic niches of the adult mammalian brain, i.e., the subventricular zone lining the lateral ventricle and the subgranular zone of the hippocampus, there exist distinct populations of proliferating neural precursor cells that differentiate to generate new neurons. Numerous studies have suggested that epigenetic regulation by histone‐modifying proteins is important in guiding precursor differentiation during development; however, the role of these proteins in regulating neural precursor activity in the adult neurogenic niches remains poorly understood. Here we examine the role of an NAD+‐dependent histone deacetylase, SIRT1, in modulating the neurogenic potential of neural precursors in the neurogenic niches of the adult mouse brain. We show that SIRT1 is expressed by proliferating adult subventricular zone and hippocampal neural precursors, although its transcript and protein levels are dramatically reduced during neural precursor differentiation. Utilizing a lentiviral‐mediated delivery strategy, we demonstrate that abrogation of SIRT1 signaling by RNAi does not affect neural precursor numbers or their proliferation. However, SIRT1 knock down results in a significant increase in neuronal production in both the subventricular zone and the hippocampus. In contrast, enhancing SIRT1 signaling either through lentiviral‐mediated SIRT1 overexpression or through use of the SIRT1 chemical activator Resveratrol prevents adult neural precursors from differentiating into neurons. Importantly, knock down of SIRT1 in hippocampal precursors in vivo, either through RNAi or through genetic ablation, promotes their neurogenic potential. These findings highlight SIRT1 signaling as a negative regulator of neuronal differentiation of adult subventricular zone and hippocampal neural precursors. © 2013 Wiley Periodicals, Inc.